PENGARUH IKLIM ORGANISASI, PELATIHAN DAN KEMAMPUAN KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI (Studi pada Perawat Rumah Sakit Jiwa Daerah Surakarta) - Suprihatmi Sri Wardiningsih, Dwi Faridayanti, Amin Wahyudi & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2017)
This research is conducted to analysis the significance effect of: (1)organisastion climate to the nurses work productivity, (2) training to thenurses work productivity, (3) work ability to the nurses work productivity. Thepopulation is entire nurse at RSJD Surakarta as many as 100 nurses. Thesample is taking by simple random sampling, so get sample as many as 80nurses. The technique of gathering the data is using questioner throughvalidity test and reliability test. The analysis technique uses doubleregression with classical assumption. The analysis result shows that:(1)regression equation Y= 2,103 + 0,290X1 + 0,651X2 + 0,600X3; (2) t testclimate organisation variable have significance value < 0,05; t test trainingvariable have significance value < 0,05; t test work ability variable havesignificance value < 0,05; So that the three independent variables have asignificant effect on work productivity of nurses. The adjusted R2 amount0,717; it means that the magnitude of influence contributions of climateorganisation, training anad work ability to nurses work productivity amount of71,7%, the rest was influenced by other variables.Keywords: organizational climate, training, work ability, nurses workproductivity